Realización de la tabla tecnológica de un acero grado 60 - Vega Guillén, Víctor (1999)
A technological table of a steel gathers various technological data as well as a series of diagrams that allow the manufacturer and the user to obtain the desirable properties in order to guarantee the commissioning of said steel. Therefore, the technological table is a complement to the classification table that classifies steels according to their chemical composition and the Standard that indicates the minimum characteristics that must be obtained with a previously established treatment. The determination of the different data that make up this table is simple and is within the reach of any laboratory or a small metallurgical industry. It should be remembered that technological data are usually indicative, given the different behavior of different castings of the same type of steel and the normal limitations of the test methods, only a statistical study will be able to reflect the real limits of the quantities tested. For the preparation of the Technological Table in a grade 60 steel, it took as a sample the one produced in our environment.